Latent Autoimmune Diabetes in Adults and Metabolic Syndrome—A Mini Review - Pan, Niansi; Yang, Shimei; Niu, Xiaohong (Frontiers in Endocrinology, 2022)
Latent autoimmune diabetes in adults (LADA) is a heterogeneous subtype of diabetes characterized by islet cell destruction mediated by islet autoimmunity and insulin resistance. Metabolic syndrome (MetS) is a state in which many risk factors for metabolic and cardiovascular diseases accumulate in an individual. Based on clinical data, this review covers the prevalence of MetS in LADA, focusing on the risk associated with and the role of insulin resistance in the development of LADA from the perspective of inflammatory factors, environmental factors, and the gut microbiota, aiming to improve our understanding of this condition.